2023
DOI: 10.19261/cjm.2023.910
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of quercetin functionalized chitosan and determination of antioxidant properties

Abstract: This paper is dedicated to the synthesis of a copolymer with reducing properties obtained by functionalizing chitosan with quercetin and determining the antioxidant activity of the derivatives obtained depending on the molar mass of the polymer. For this purpose, low molecular weight chitosan was obtained by oxidizing commercial chitosan with hydrogen peroxide and further functionalization with quercetin by the covalent grafting method. The functionalization process was performed through the following steps: f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…These findings suggest that this composite can effectively prevent the oxidation of different organic substrates. As such, it can be used in various industries such as cosmetics, food, and pharmaceuticals to protect products from oxidative damage (Gonta et al, 2023). In studies conducted on HepG2 cancer cells using QUR/CS nanohydrogels, it was found that QUR in nanogels can significantly decrease DNA methyltransferase expression and augment DNA methylation (Abbaszadeh et al, 2020).…”
Section: Nanotechnology Solutions As a Promising Practical Approach I...mentioning
confidence: 99%
“…These findings suggest that this composite can effectively prevent the oxidation of different organic substrates. As such, it can be used in various industries such as cosmetics, food, and pharmaceuticals to protect products from oxidative damage (Gonta et al, 2023). In studies conducted on HepG2 cancer cells using QUR/CS nanohydrogels, it was found that QUR in nanogels can significantly decrease DNA methyltransferase expression and augment DNA methylation (Abbaszadeh et al, 2020).…”
Section: Nanotechnology Solutions As a Promising Practical Approach I...mentioning
confidence: 99%